If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + 4 + -2m = 4m Reorder the terms: 4 + 7m + -2m = 4m Combine like terms: 7m + -2m = 5m 4 + 5m = 4m Solving 4 + 5m = 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 4 + 5m + -4m = 4m + -4m Combine like terms: 5m + -4m = 1m 4 + 1m = 4m + -4m Combine like terms: 4m + -4m = 0 4 + 1m = 0 Add '-4' to each side of the equation. 4 + -4 + 1m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1m = 0 + -4 1m = 0 + -4 Combine like terms: 0 + -4 = -4 1m = -4 Divide each side by '1'. m = -4 Simplifying m = -4
| 2*4-2*11=x(4-11) | | -7v+35=7(v+3) | | a+2b=cforb | | x*x*x-3x+2=0 | | 5p+2=4p-8 | | -45=-15y | | 9x-2=8X-4 | | -10-m=2m+5 | | -17=x+(-12) | | 2x+9x-6x=18+2 | | -3.82+2.83= | | 2a-b=cfora | | u+10=6u-10u-10 | | 5m^2-27=40 | | 7(-3r-1)+3r=137 | | -200=-8h | | 3y^3-15y^2-2y=0 | | 8+3x=5x+70 | | k-26=-37 | | 8-2cosx=0 | | 4b+2b+b+3=10 | | 35x+3-(-2)=75 | | 2(3x-4)=76 | | 3X^2=5x-14 | | -7=-19-a | | y=45x+30 | | a+2b=cfora | | 4x+5+6x+9=124 | | 3x+50y=450 | | 12=n+(-10) | | 5+6N=41 | | 2(n-6)=15 |